Implementasi UI/UX Aplikasi Mobile Teepties untuk Monitoring Perkembangan Siswa SDIT Bina Auladi Menggunakan Metode Design Thinking - Khariyyah, Nabilah; Panji, Krisna; Pramudiawardani, Shelly (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
This study aims to design the user interface and user experience (UI/UX) for a mobile application called TeepTies, which monitors student development at SDIT Bina Auladi. The main problem identified at the school is the lack of structured communication between teachers and parents regarding students’ development, especially in non-academic aspects. The Design Thinking method was chosen because it focuses on user needs and encourages innovative solutions through an iterative process that involves a deep understanding of the problem. This study follows the five stages of Design Thinking: empathize, define, ideate, prototype, and test. The design resulted in a mobile-based prototype application featuring academic and non-academic development reports, attendance, direct messaging, and announcements. Evaluation was conducted through usability testing and the System Usability Scale (SUS), with an average score of 72.3, which falls into the "Acceptable" category, indicating that users will receive the application design. TeepTies is expected to become an effective digital solution in enhancing collaboration between teachers and parents in monitoring students' development at school.